1996
DOI: 10.1088/0954-3899/22/7/015
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic gamma rays from the Large Magellanic Cloud - and from the Galaxy

Abstract: An analysis has been made of gamma rays from the Large Magellanic Cloud (LMC) using data from the Compton Gamma Ray Observatory. After correcting for foreground gamma rays from cosmic ray (CR) interactions in our own Galaxy it is found that the gamma ray intensity maps show a displacement of peak position away from the peak of the atomic gas contours and towards the peak of the starlight contours. An explanation is advanced in terms of there being an increasing contribution from inverse Compton interactions, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Fichtel et al 1991;Bertsch et al 1993;Mori 1997;Hunter et al 1997). However, according to our Monte Carlo result and the observed data given by Al-Dargazelli et al (1996a), the -ray integral flux with energy greater than 1 GeV from the pulsars in the LMC is about 95 per cent of the observed diffuse -ray flux with energy greater than 1 GeV from the LMC. It seems that the energy spectrum of cosmic-ray protons should be steeper than that in our Galaxy at least in the high-energy range, or that the ratio of cosmic-ray electrons to cosmic-ray protons is different from that in our Galaxy.…”
Section: O N C Lu S I O N S a N D Discussion Ssupporting
confidence: 72%
See 3 more Smart Citations
“…Fichtel et al 1991;Bertsch et al 1993;Mori 1997;Hunter et al 1997). However, according to our Monte Carlo result and the observed data given by Al-Dargazelli et al (1996a), the -ray integral flux with energy greater than 1 GeV from the pulsars in the LMC is about 95 per cent of the observed diffuse -ray flux with energy greater than 1 GeV from the LMC. It seems that the energy spectrum of cosmic-ray protons should be steeper than that in our Galaxy at least in the high-energy range, or that the ratio of cosmic-ray electrons to cosmic-ray protons is different from that in our Galaxy.…”
Section: O N C Lu S I O N S a N D Discussion Ssupporting
confidence: 72%
“…Fig. 3 shows the comparison of expected integrated flux from pulsars with various energies, where the solid curve represents the expected flux from the pulsars in the LMC and the observed data are taken from -Dargazelli et al (1996a). It can be seen that the contribution from the pulsars in the LMC becomes more important as the energy increases.…”
Section: R E S U Lt Smentioning
confidence: 99%
See 2 more Smart Citations
“…The Large Magellanic Cloud (LMC) was studied by Sreekumar et al (1992) and Chi and Wolfendale (1993) with dramatically different results; the former inferred that the CR intensity was the same in both the Galaxy and the LMC, whereas the latter concluded that the CR intensity in the LMC was only ∼15% of that in the Galaxy. In a very recent paper (Al-Dargazelli and Wolfendale 1996) we have examined the LMC in detail and pinpointed the reasons for the differences. Not surprisingly, perhaps, we prefer the result of Chi and Wolfendale (1993), albeit with some small changes.…”
Section: Introductionmentioning
confidence: 99%